2016
DOI: 10.1177/2156587215610032
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Properties and Effect of Quercetin and Its Glycosylated Form (Rutin) on Acetylcholinesterase and Butyrylcholinesterase Activities

Abstract: This study sought to investigate the anticholinesterase and antioxidative properties of quercetin and its glycosylated conjugate, rutin. The in vitro inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activities, inhibition of Fe 2þ -induced lipid peroxidation in rat's brain homogenates, radicals scavenging, and Fe 2þ -chelating abilities of the flavonoids were investigated in vitro with concentrations of the samples ranging from 0.06 to 0.6 mM. Quercetin had significantly higher AChE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 26 publications
7
69
0
Order By: Relevance
“…Earlier study from our laboratory [43] re ported that caffeic acid and chlorogenic acid inhibited AChE and BChE activities in vitro, with caffeci acid producing the significantly higher inhibitory effects; nevertheless, their combination was reported to pro duce antagonistic effects on the enzymes' inhibition. Furthermore, Ademosun et al, [44] reported that quercetin had significantly higher cholinesterase inhibitory effects than its glycosylated form (rutin). Therefore, in this study, interactions between the constituent phenolic phytochemicals in the extracts could also contribute significantly to the observed enzyme inhibitory effects.…”
Section: Resultsmentioning
confidence: 98%
“…Earlier study from our laboratory [43] re ported that caffeic acid and chlorogenic acid inhibited AChE and BChE activities in vitro, with caffeci acid producing the significantly higher inhibitory effects; nevertheless, their combination was reported to pro duce antagonistic effects on the enzymes' inhibition. Furthermore, Ademosun et al, [44] reported that quercetin had significantly higher cholinesterase inhibitory effects than its glycosylated form (rutin). Therefore, in this study, interactions between the constituent phenolic phytochemicals in the extracts could also contribute significantly to the observed enzyme inhibitory effects.…”
Section: Resultsmentioning
confidence: 98%
“…From the IC 50 values listed in Table , SA displayed higher inhibitory effect against both cholinesterases than QU. The flavonoid content of SA and the presence of quercetin in conjunction with chlorogenic and caffeic acids, which have been demonstrated to be potent inhibitor of cholinesterases (Ademosun et al, ; Oboh, Agunloye, Akinyemi, Ademiluyi, & Adefegha, ; Sriraksa et al, ), could have (but not completely) responsible for this effects. Although, this effect could be considered lower than that of the synthetic inhibitors, such as galantamine (IC 50 for AChE = 0.14 μg/mL) or huperzine A (IC 50 = 10 −4 μM) (Mukherjee, Kumar, Mal, & Houghton, ; Wszelaki, Kuciun, & Kiss, ), but the adverse effects exhibited by these synthetic drugs/inhibitors may not be experience using plants or plant‐based inhibitors such as the plants in use (Ademosun et al, ; Chaiyana & Okonogi, ; de Paula et al, )…”
Section: Resultsmentioning
confidence: 99%
“…The research on herbal plants are on the increase, focusing on the preparation of alternative pharmaceutical ingredients for the management of several human ailments (Ceylan et al, ; Hirasa & Takemasa, ). The interest in finding natural cholinesterases (ChEs) inhibitors for the management of cognitive/mental disorders is on the increase as studies have shown that polyphenolic compounds such as quercetin, rutin among others could of health benefits (Ademosun, Oboh, Bello, & Ayeni, ; Gironés‐Vilaplana et al, ; Khan et al, ; Nwanna et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin (0.1‐0.4 mmol/L) has also been reported to significantly inhibit AChE (IC 50 = 0.18 mmol/L) and BChE (IC 50 = 0.203 mmol/L) along with a strong inhibition of Fe (2+) ‐induced lipid peroxidation and radical scavenging abilities in rats’ brain homogenates . The inhibition of cholinesterases (ChEs) and antioxidative properties are possible mechanisms of action of quercetin for the management of oxidative stress‐induced neurodegeneration.…”
Section: Quercetinmentioning
confidence: 99%